CORRELATION BETWEEN LUMBO SACRAL ANGLE AND PRORIOCEPTION IN SUBJECTS WITH CHRONIC LOW BACK PAIN (Asian Journal of Medical Research and Health Sciences, 2023)
Background: Chronic low back pain is a significant issue that is only becoming worse, partly as a result of the age-ing and expanding global population. It affects people of all ages and is typically linked to sedentary jobs, tobacco use, obesity, and low socioeconomic status. According to Andersons et al., the point prevalence of LBA in adults is estimated to be 30%, with the yearly incidence at 15%. Objective: To determine the correlation between lumbosacral angle and proprioception in subjects with chronic low back pain. Methods: A total of 175 subjects have been recruit-ed for the study out of which 120 subjects with CLBA who met the selection criteria were included in the study. The subjects who reported having chronic low back pain without any radio-graphically visible abnormalities were taken into consideration; the VAS score and chronicity were also gathered to gauge the severity of the pain. Lumbosacral angle and Proprioception were recorded. Results: For males and females, the correlation between LSA and VAS has an r-value of -0.131 and 0.144. It was discovered that there was no correlation between the two (p>0.05).In men, the association between VAS and sickness duration has an r-value of 0.122, while in women, it has an r-value of -0.134. Both are discovered to be not significant (p>0.05). Conclusion: There is a positive correlation between joint proprio-ception impairment and chronicity in CLBP patients. This correlation was found to be more pronounced in females than in males in (JPE) lumbar flexion movement and significant in both males and females in (JPE) lumbar extension movement.